Role of NF‐κB activation and Th1/Th2 imbalance in pulmonary toxicity induced by nano NiO. Issue 4 (28th July 2016) - Chang, Xuhong; Zhu, An; Liu, Fangfang; Zou, Lingyue; Su, Li; Li, Sheng; Sun, Yingbiao
ABSTRACT: With the progress of nanotechnology, nano nickel oxide (NiO) has been extensively used as sensors, battery electrodes, catalysts, and cosmetics. Previous researches verified that nano NiO could exert pulmonary toxicity, but its mechanism was unclear. To shed light upon this, the role of nuclear factor‐ κ B (NF‐ κ B) activation and Th1/Th2 imbalance were to explore in pulmonary damage induced by nano NiO. Male Wistar rats were randomized into control group, nano NiO groups (0.015, 0.06, and 0.24 mg kg −1 ) and micro NiO group (0.024 mg kg −1 ) and treated by intratracheal instillation twice a week for 6 weeks. The results showed that the abnormal changes induced by nano NiO were found on indicators of nitrative stress (NO, TNOS, and iNOS), inflammatory cytokines (TNF‐ α, IL‐2, and IL‐10) and cytokine‐induced neutrophil chemoattractants (CINC‐1, CINC‐2 αβ, and CINC‐3) in lung tissue. In addition, nano NiO instillation induced the upregulated mRNA and protein expression of NF‐ κ B, inhibitor of κB kinase‐ α (IKK‐ α ) and nuclear factor‐inducing kinase (NIK). The protein content of GATA‐3 increased as well as T‐bet decreased in nano NiO groups, and the ratio of T‐bet/GATA‐3, as a key evaluation indicator of Th1/Th2 balance, was lower than the control group. The findings indicated that nano NiO could enhance the nitrative stress and inflammatory response in lung tissue, and its mechanism was related to the NF‐ κ B activation and Th1/Th2 imbalance. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1354–1362, 2017.